Electromagnetic Energy Harvester with Embedded Ferrofluid In PCB Technology - Chiu, Yi; Hong, Hao-Chiao (My University, 2018)
This paper reports an electromagnetic energy harvester fabricated with Rigid-Flex Printed Circuit Board (PCB) technology by a commercial PCB supplier. Rigid FR-4 boards were used for transduction coil routing and mechanical support; flexible polyimide (PI) films were used to design elastic springs and magnet mounting platforms. Ferrofluid (FF) was injected into the embedded cavities inside the rigid PCB to increase the effective permeability of the medium around the magnet and thus increase the induced electromotive force (emf). Experiments showed up to 70% increase of output emf and 190% increase of output power compared with harvesters without embedded ferrofluid.